Scalp electrode placement accuracy for the canine electroencephalography array - Everest, Stephen; St-Denis, Myles; Dony, Robert; Gaitero, Luis; Linden, Alexander Zur; Cortez, Miguel A.; Parmentier, Thomas; James, Fiona M. K. (Frontiers in Veterinary Science, 2025)
IntroductionDespite the common occurrence of idiopathic epilepsy amongst neurological conditions in dogs, electroencephalography (EEG), the gold standard for seizure detection, is relatively neglected. The use of EEG in veterinary medicine is rudimentary compared to that in human medicine, particularly with respect to the quantification of EEG electrode placement error, i.e., the accuracy of electrode placement relative to the diverse canine cortical topography.MethodsTherefore, we quantified the intra-observer EEG electrode placement error using a single canine EEG electrode placement array, on virtual models of head and brain created from archived computed tomographic scans of Brachycephalic (n = 5), Mesocephalic (n = 15) and Dolichocephalic (n = 5) dogs from breeds with archetypal skull conformation. For the Mesocephalic cohort, a stereotactic brain atlas was incorporated into the brain models to quantify electrode placement error via a universal coordinate system. As this was not possible for the Brachycephalic and Dolichocephalic cohort, instead electrode placement was described in relation to cortical landmarks.ResultsGaps in cortical coverage between cohorts were identified, such as poor coverage of the olfactory and frontal regions in the brachycephalic cohort and the parietal region in the Mesocephalic and Dolichocephalic cohorts. Quantitative analysis of electrode placement in the Mesocephalic cohort showed the minimum variance of electrode localization for the x coordinate of the F8 electrode (0.8 mm) and the greatest variance for the y coordinate of the Cz electrode (35.2 mm).DiscussionThis is the first study to highlight the knowledge gaps regarding the accuracy of canine EEG electrode localization, differences in the array coverage across the diverse canine skull conformations, and the urgent need for a stereotactic brain atlas for specific canine skull conformations.